基于开端同轴探头技术的肺癌转移和非转移淋巴结介电特性 (Nan Fang Yi Ke Da Xue Xue Bao, 2019)
OBJECTIVE: To investigate the differences in dielectric properties (relative dielectric constant and conductivity) between metastatic and non-metastatic lymph nodes (LNs). METHODS: An open-end coaxial probe (1 MHz to 4 GHz) was used to measure the dielectric properties of the LNs obtained from 76 lung cancer patients. According to the results of pathological examination, the LNs were divided into metastatic and non-metastatic LNs, and the metastatic LNs were divided into lung squamous cell carcinomas and adenocarcinoma. The differences in dielectric properties of the LNs were analyzed at 1 MHz to 4 GHz and at 6 single frequencies (64, 128, 298, 433, 915, and 2450 MHz). RESULTS: The metastatic LNs showed higher dielectric properties than non-metastatic LNs in the frequency range from 1 MHz to 4 GHz. No significant differences were found in the dielectric properties between metastatic LNs of lung squamous cell carcinoma and adenocarcinoma. At the 6 single frequencies, the metastatic and non-metastatic LNs showed significant differences in their dielectric properties (P < 0.01). CONCLUSION: The open-ended coaxial probe technology is not capable of identifying the pathological type of the primary lung cancer from which the metastatic LNs are derived, but it can identify the differences in dielectric properties between metastatic and non-metastatic LNs, and thus provide a reliable means for identification of LN metastasis of lung cancer.